Response to Achieving consensus in the measurement of psychological adjustment to cleft lip and/or palate at age 8+ years - Harrison, CJ; Dalton, L; Goodacre, TEE; Swan, MC (SAGE Publications, 2020)
In this letter, we discuss the recently published paper by Stock et al, entitled Achieving Consensus in the Measurement of Psychological Adjustment to Cleft Lip and/or Palate at Age 8+ Years.